Mixed Stieltjes–Hilbert and Fourier Sine and Cosine Convolutions - Nguen, Suan Thao (Ukrains’kyi Matematychnyi Zhurnal, 2001)
We introduce generalized convolutions of Stieltjes, Hilbert, and Fourier sine and cosine transforms and consider their applications to integral equations.